2015
DOI: 10.1007/s12540-015-1020-x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction separation of Zr and Hf from nitric acid solutions by PC 88A and its mixture with other extractants

Abstract: Solvent extraction for the separation of zirconium and hafnium from strong nitric acid solution has been investigated by using several organophosphorous acids (D2EHPA, PC 88A and Cyanex 272) and its mixture. Among the single extractants, PC 88A showed the best performance for the extraction and separation of the two metals. Mixtures of PC 88A with neutral, cationic and anionic extractants were tested in order to improve the separation between Zr and Hf. Mixtures of PC 88A with TBP or Versatic 10 or TOA did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
6
0
2
Order By: Relevance
“…The investigation on the separation and extraction behavior of Zr(IV) and Hf(IV) from hydrochloric, nitric and sulfuric acid solutions by using cationic, neutral and amine-based extractants have been investigated in our previous work. [8][9][10][11][12][13][14][15] Based on this work, it was demonstrated that Zr(IV) is selectively extracted over Hf(IV) from strong hydrochloric or nitric acid solutions by cationic, neutral and amine extractants. [9][10][11][12][13] On the other hand, selective extraction of Hf(IV) over Zr(IV) occurs from only strong sulfuric acid solutions (1-4 M) by using acidic organophosphorus extractants.…”
Section: )mentioning
confidence: 92%
See 1 more Smart Citation
“…The investigation on the separation and extraction behavior of Zr(IV) and Hf(IV) from hydrochloric, nitric and sulfuric acid solutions by using cationic, neutral and amine-based extractants have been investigated in our previous work. [8][9][10][11][12][13][14][15] Based on this work, it was demonstrated that Zr(IV) is selectively extracted over Hf(IV) from strong hydrochloric or nitric acid solutions by cationic, neutral and amine extractants. [9][10][11][12][13] On the other hand, selective extraction of Hf(IV) over Zr(IV) occurs from only strong sulfuric acid solutions (1-4 M) by using acidic organophosphorus extractants.…”
Section: )mentioning
confidence: 92%
“…[8][9][10][11][12][13][14][15] Based on this work, it was demonstrated that Zr(IV) is selectively extracted over Hf(IV) from strong hydrochloric or nitric acid solutions by cationic, neutral and amine extractants. [9][10][11][12][13] On the other hand, selective extraction of Hf(IV) over Zr(IV) occurs from only strong sulfuric acid solutions (1-4 M) by using acidic organophosphorus extractants. 8,14) In this work, solvent extraction experiments were carried out from sulfuric acid solutions by using several acidic extractants, such as Versatic acid, LIX 63, Cyanex 301 and their mixtures with TBP.…”
Section: )mentioning
confidence: 92%
“…Kemiripan dan perbedaan keduanya terletak pada jari-jari ionzirkonium sebesar 0,74 o A dan hafnium sebesar 0,75 o A. Densitas Zr = 6,49 g/cm 3 dan Hf = 13,31 g/cm 3 , nomor atom Zr = 40 dan Hf = 91,2. Beberapa metode yang telah dilakukan untuk pemisahan unsur Zr dengan Hf adalah proses fraksinasi kristalisasi [4,6] , pertukaran ion [2,3,4,8,9,10] , fraksinasi distilasi [2] , termal difusi [2] , ekstraksi pelarut [1,3,4,5,6,11,[14][15][16][17][18][19] dan proses elektro kimia [2] . Laddha (1976) menyatakan bahwa proses ekstraksi lebih ekonomis digunakan untuk pemisahan campuran bahan dengan sifat kimia yang miripantara satu dengan yang lain dibandingkan dengan proses distilasi [12] .…”
Section: Pendahuluanunclassified
“…Atas dasar pertimbangan kemudahan dan laju proses, kemur-nian produk yang tinggi, efektif dan selektivitas yang tinggi, maka metoda ini semakin bersaing dengan metode pemi-sahan lainnya. Solven yang digunakan untuk ekstraksi pada pemisahan zirkonium dan hafnium yaitu tributil fosfat (TBP) [1,3,4,5,6,9,11,14,16,21] , metil isibutil keton (MIBK) [3,5,6] , D2EHPA [6,18] , cyanex [18] , Aliquat 336 [3] dengan pengencer kerosene, n heptan, dodekan, xylen dan eter [4,6,11] .…”
Section: Pendahuluanunclassified
“…Zirconium (Zr) is considered as vital material in the nuclear industry [1]. This metal and its alloys are utilized as a construction material for nuclear reactors and as fuel rod cladding [2][3][4]. Zirconium has a unique combination of the physical and chemical characteristics such as suitable thermal conductivity, corrosion resistance, and low thermal neutron capture cross-section (0.18 barns) [1,5].…”
Section: Introductionmentioning
confidence: 99%